Evaluating multi‐step oxidative stabilization behavior of coal tar pitch‐based fiber. Issue 11 (30th September 2020) - Niu, Hao; Zuo, Pingping; Shen, Wenzhong; Qu, Shijie
Abstract: Oxidative stabilization is an important step for isotropic pitch‐based carbon fiber preparation; coal tar pitch‐based fiber is treated by multi‐step oxidative stabilization under various conditions to investigate the oxidative stabilization mechanism. The chemical structure changes of isotropic pitch‐based fiber during the oxidative stabilization and carbonization stage are systematically characterized by In‐situ diffuse reflectance infrared Fourier transform, elemental analysis, mass spectroscopy, X‐ray photoelectron spectroscopy, nuclear magnetic resonance, scanning electron microscope with an energy dispersive X‐ray spectrometer. These results show that the oxygen distribution gradient in oxidative stabilized fiber radial direction become homogeneously with the increasing of oxidation temperature and time under multi‐step oxidative stabilization. The resultant carbon fiber shows tensile strength of 942 ± 42 MPa and Young's modulus of 42.8 ± 3.1 GPa due to appropriate oxygen content, homogeneous oxygen distribution, more cross‐link bond (C‐O‐C) content, higher aromaticity and lower weight loss introduced in multi‐step oxidative stabilized pitch fiber. The multi‐step oxidative stabilization provides synergy effect between reaction rate and the oxygen diffusion rate as well as eliminates the oxygen concentration gradient, it provides an time‐saving and energy‐effective method for the oxidative stabilization of isotropic pitch‐based carbon material (pitch fiber, pitch microsphere, etc.) and improve the resultant carbon material performance. Abstract :